2021
DOI: 10.5964/jnc.6931
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a numeracy intelligent tutoring system in kindergarten: A conceptual replication

Abstract: Intelligent Tutoring Systems are a genre of highly adaptive software providing individualized instruction. The current study was a conceptual replication of a previous randomized control trial that incorporated the intelligent tutoring system Native Numbers, a program designed for early numeracy instruction. As a conceptual replication, we kept the method of instruction, the demographics, the number of kindergarten classrooms (n = 3), and the same numeracy and intrinsic motivation screeners as the original stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 87 publications
0
2
0
Order By: Relevance
“…Likewise, of the three studies that were identified in the highly effective intervention set (Grimes et al, 2020; Kosko & Ferdig, 2016; Wu, 2020), two used a researcher developed assessment of mathematical attainment as the primary outcome measure. Within this QCA, these issues cannot be statistically controlled for.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, of the three studies that were identified in the highly effective intervention set (Grimes et al, 2020; Kosko & Ferdig, 2016; Wu, 2020), two used a researcher developed assessment of mathematical attainment as the primary outcome measure. Within this QCA, these issues cannot be statistically controlled for.…”
Section: Discussionmentioning
confidence: 99%
“…Eight apps were suitable for this analysis (see Figure S1). The associated included studies focused on typically developing children aged between 4 and 7 years old with an experimental design (randomised control trial or quasi‐experimental design) (Berkowitz et al, 2015; Cary et al, 2020; Grimes et al, 2020; Kosko & Ferdig, 2016; Outhwaite et al, 2018; Schacter & Jo, 2017; Spencer, 2013; Wu, 2020). Two studies reported subgroup analyses on children identified as underachieving in mathematics (Cary et al, 2020; Wu, 2020).…”
Section: Methodsmentioning
confidence: 99%